Pengaruh Diplomasi Mineral Kritis Tiongkok Terhadap Kebijakan Hirilisasi Nikel Indonesia - Aurelia Marlin Kattu Taula’bi’ (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of China’s critical mineral diplomacy on Indonesia’s nickel downstreaming policy during the 2014–2024 period. Critical minerals, particularly nickel, have become strategic commodities in the global energy transition due to their role in electric vehicle batteries and renewable energy industries. Indonesia, as the country with the largest nickel reserves, has implemented a downstreaming policy to increase added value and strengthen its position in the global supply chain. However, the implementation of this policy cannot be separated from China’s involvement as the main investor in Indonesia’s nickel processing sector. This research employs a qualitative method with an explanatory approach through literature study. The findings indicate that China’s critical mineral diplomacy is carried out through foreign direct investment, industrial infrastructure development, technology transfer, and global supply chain integration. This diplomacy contributes to accelerating Indonesia’s downstreaming policy but also creates dependency on foreign capital and technology. Therefore, Indonesia’s downstreaming policy is influenced not only by domestic factors but also by international political economy dynamics.